Transcript Profiling Reveals the Presence of Abiotic Stress and Developmental Stage Specific Ascorbate Oxidase Genes in Plants - Batth, Rituraj (Front Plant Sci, 2017)
Abiotic stress and climate change is the major concern for plant growth and crop yield. Abiotic stresses lead to enhanced accumulation of reactive oxygen species (ROS) consequently resulting in cellular damage and major losses in crop yield. One of the major scavengers of ROS is ascorbate (AA) which acts as first line of defense against external oxidants. An enzyme named ascorbate oxidase (AAO) is known to oxidize AA and deleteriously affect the plant system in response to stress. Genome-wide analysis of AAO gene family has led to the identification of five, three, seven, four, and six AAO genes in Oryza sativa, Arabidopsis, Glycine max, Zea mays, and Sorghum bicolor genomes, respectively. Expression profiling of these genes was carried out in response to various abiotic stresses and during various stages of vegetative and reproductive development using publicly available microarray database. Expression analysis in Oryza sativa revealed tissue specific expression of AAO genes wherein few members were exclusively expressed in either root or shoot. These genes were found to be regulated by both developmental cues as well as diverse stress conditions. The qRT-PCR analysis in response to salinity and drought stress in rice shoots revealed OsAAO2 to be the most stress responsive gene. On the other hand, OsAAO3 and OsAAO4 genes showed enhanced expression in roots under salinity/drought stresses. This study provides lead about important stress responsive AAO genes in various crop plants, which could be used to engineer climate resilient crop plants.